2014
DOI: 10.1002/jcp.24618
|View full text |Cite
|
Sign up to set email alerts
|

Role of PUF‐8/PUF Protein in Stem Cell Control, Sperm‐Oocyte Decision and Cell Fate Reprogramming

Abstract: Pumilio and FBF (PUF) proteins are conserved stem cell regulators that maintain germline stem cells (GSCs) in worms and flies. Moreover, they are also present in vertebrate stem cells. The nematode Caenorhabditis elegans has multiple PUF proteins with specialized roles. Among them, PUF-8 protein controls multiple cellular processes, including proliferation, differentiation, sperm-oocyte decision, and cell fate reprogramming, depending on the genetic context in the C. elegans germline. In this review, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…It was previously reported that PUF-8 also represses GLP-1/Notch-mediated germline proliferation (Racher and Hansen, 2012; Datla et al, 2014) (Fig. 5A): while glp-1(ar202gf) mutants produce both sperm and oocyte, which are self-fertile at 20°C, the puf-8 mutation strongly enhances the germline tumor phenotype of the glp-1(ar202gf) mutant even at 20°C (Racher and Hansen, 2012) (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…It was previously reported that PUF-8 also represses GLP-1/Notch-mediated germline proliferation (Racher and Hansen, 2012; Datla et al, 2014) (Fig. 5A): while glp-1(ar202gf) mutants produce both sperm and oocyte, which are self-fertile at 20°C, the puf-8 mutation strongly enhances the germline tumor phenotype of the glp-1(ar202gf) mutant even at 20°C (Racher and Hansen, 2012) (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Interestingly, we found that the Glp phenotype of fbf-1 fbf-2 mutants was sufficiently suppressed by additional removal of PUF-8 (another PUF protein) (Fig. 5A and 5B), a key regulator for C. elegans germline development (Subramaniam and Seydoux, 2003; Ariz et al, 2009; Cha et al, 2012; Racher and Hansen, 2012; Pushpa et al, 2013; Vaid et al, 2013; Datla et al, 2014; Sorokin et al, 2014; Priti and Subramaniam, 2015). The puf-8 fbf-1 fbf-2 triple mutants displayed mitotically dividing cells in the germline (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…4E) (Morgan et al, 2010;Cha et al, 2012;Datla et al, 2014). Surprisingly, inhibition of Ras-ERK MAPK signaling by either genetic mutation or drug treatment (e.g., U0126) sufficiently rescued puf-8; lip-1 sterility (Morgan et al, 2010;Cha et al, 2012;Datla et al, 2014). Therefore, mpk-1(lf) mutants and puf-8; lip-1 mutants (Table 1) are useful animals for the identification of drugs that may target Ras-ERK MAPK signaling positively or negatively (Fig.…”
Section: Elegans Ras Signalingmentioning
confidence: 96%
“…In addition, activated MPK-1/ERK in puf-8; lip-1 mutant promotes spermatogenesis without switching into oogenesis (Masculinization of germline (Mog) phenotype) at 20°C and develops germline tumors via dedifferentiation of spermatocytes at 25°C (Fig. 4E) (Morgan et al, 2010;Cha et al, 2012;Datla et al, 2014). Surprisingly, inhibition of Ras-ERK MAPK signaling by either genetic mutation or drug treatment (e.g., U0126) sufficiently rescued puf-8; lip-1 sterility (Morgan et al, 2010;Cha et al, 2012;Datla et al, 2014).…”
Section: Elegans Ras Signalingmentioning
confidence: 97%
“…Advances in addressing the integration of regulatory information through systems biology strategies can provide valuable insight into both the biology and pathology of cell cycle control (Hartmann and Schreiber, ; Oberhardt and Gianchandani, ; Tortolina et al, ; De Oliveira Dal'Molin et al, ; Mason and Watt, ; Petrey et al, ; Roy and Singer, ; Yang et al, ; Zhu et al, ). Integration of regulatory activities that mediate cell cycle and cell growth control, as well as regulate proliferation with competency for expression of phenotype, are fundamentally important for biological processes and cancer (Lamerton, ; Aguilar et al, ; Datla et al, ; Dudakovic et al, ; Gordon et al, ; Jongsma et al, ; Lopez‐Camacho et al, ; Lopez‐Mejia and Fajas, ; Mundade et al, ; Stumpff et al, ; Voskas et al, ; Weber and Ryan, ; Asghar et al, ; Faulknor et al, ; Fu et al, ; Kapinas et al, ; Meadows and Millar, ; Schwanbeck, ; Sharma et al, ; Stachowiak et al, ; Sun et al, ; Vadia and Levin, ). Dysfunction in the cell cycle linked integrated control of both cell proliferation and cell differentiation is involved in the early stages of carcinogenesis (Scott and Florine, ; Wille et al, ; Scott and Maercklein, ; Wier and Scott, ; Sparks et al, ; Wille and Scott, ; Scott et al, ; Weinstein, ).…”
mentioning
confidence: 99%